Striking a Balance: Navigating Privileges, Immunities, and Accountability in International Organizations (Dhaka University Law Journal, 2024)
This paper delves into the nuanced landscape of Privileges and Immunities (P&Is) granted to international organizations (IOs) and the contentious issue of denial of justice. Critically analyzing this aspect, the paper justifies the criticism by dissecting key international instruments that aim to balance protection and accountability. It examines the limitations of IO immunity, the concept of waiver, administration of justice, cooperation with member states, and provisions to prevent justice abuse. The debate over determining the functional nature of IO acts is explored, considering the dangers of empowering member states and national courts. The paper concludes by suggesting a recalibration of the current system to strike a more equitable balance.Dhaka University Law Journal, 2023, 34 (2), 97-113